2021
DOI: 10.1080/15476286.2020.1869892
|View full text |Cite
|
Sign up to set email alerts
|

Mapping rRNA 2’-O-methylations and identification of C/D snoRNAs in Arabidopsis thaliana plants

Abstract: In all eukaryotic cells, the most abundant modification of ribosomal RNA (rRNA) is methylation at the ribose moiety (2ʹ-O-methylation). Ribose methylation at specific rRNA sites is guided by small nucleolar RNAs (snoRNAs) of C/D-box type (C/D snoRNA) and achieved by the methyltransferase Fibrillarin (FIB).Here we used the Illumina-based RiboMethSeq approach for mapping rRNA 2ʹ-O-methylation sites in A. thaliana Col-0 (WT) plants. This analysis detected novel C/D snoRNA-guided rRNA 2ʹ-O-methylation positions an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 75 publications
1
36
0
Order By: Relevance
“…However, future studies are required to explore whether this is a unique modification or whether ITS1, ITS2 and the ETS regions are generally modified, and to understand the role of modifications of the pre-rRNA. A complementary analysis using RiboMethSeq for detection of 2′-O-ribose-me modifications yielded novel modification sites as well ( Azevedo-Favory et al, 2020 ).…”
Section: The Rrna Modification In Plantsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, future studies are required to explore whether this is a unique modification or whether ITS1, ITS2 and the ETS regions are generally modified, and to understand the role of modifications of the pre-rRNA. A complementary analysis using RiboMethSeq for detection of 2′-O-ribose-me modifications yielded novel modification sites as well ( Azevedo-Favory et al, 2020 ).…”
Section: The Rrna Modification In Plantsmentioning
confidence: 99%
“…Different approaches exploring the modifications of the rRNA in Arabidopsis yielded a total of 321 rRNA modification sites ( Barneche et al, 2001 ; Qu et al, 2001 ; Chen and Wu, 2009 ; Kim et al, 2010 ; Sun et al, 2019 ; Azevedo-Favory et al, 2020 ; Streit et al, 2020 ). A total of 79 2′-O-ribose-me and 43 pseudouridylation sites were assigned for the 18S rRNA, of which 44 2′-O-ribose-me and 28 pseudouridylation sites were experimentally confirmed.…”
Section: The Rrna Modification In Plantsmentioning
confidence: 99%
See 2 more Smart Citations
“…The snoRNAs identified here are all C/D-box members. Prediction and experimental identification of their targets (Table 1; Azevedo-Favory et al, 2021;Lowe and Eddy, 1999;Van Bel et al, 2018;Wu et al, 2021;Yoshihama et al, 2013) has suggested an involvement of RBP45D in 18S and 25S rRNA Nm. However, reverse transcription at low dNTP levels, followed by PCR (RTL-P; Dong et al, 2012), suggested that Nm of A1731 and A1735 of 18S rRNA and A945 of 25S rRNA (targets of snoR6-3, snoR6-2 and snoR12-1a, respectively) was not significantly altered in rpb-ko and rls6 mutants compared to their WT (Figure S6C,D), nor was the 18S or 25S rRNA maturation pattern (Figure S6E).…”
Section: Rbp45d Is a Nuclear Protein That Binds To Snrnas And Snornasmentioning
confidence: 99%